2014
DOI: 10.1007/s13224-014-0645-x
|View full text |Cite
|
Sign up to set email alerts
|

LDH (Lactate Dehydrogenase): A Biochemical Marker for the Prediction of Adverse Outcomes in Pre-eclampsia and Eclampsia

Abstract: LDH is the earliest marker seen in blood during hypoxia and oxidative stress. It is a useful biochemical marker that reflects the severity of and the occurrence of complications of PE & E; these are preventable if identified at an earlier stage and adequately managed at a higher center. Test is easily available, so screening of all cases of PE & E with LDH levels must be made mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…4 Lactate dehydrogenase (LDH) is an intracellular enzyme which converts lactic acid to pyruvic acid and its elevated levels indicates cellular death and leakage of enzyme from the cell .Increased levels of LDH were found in association with preeclampsia in a limited numbers of studies. 5 In Sudan there are many studies conducted among pregnant women suffering from pregnancy complication. [6][7][8][9] Present study is first one conducted among Sudanese women to examine the frequency symptoms occurring in severe preeclamptic patients according to the levels of GGT and LDH, indicating multiorgan involvement and severity of the disease.…”
mentioning
confidence: 99%
“…4 Lactate dehydrogenase (LDH) is an intracellular enzyme which converts lactic acid to pyruvic acid and its elevated levels indicates cellular death and leakage of enzyme from the cell .Increased levels of LDH were found in association with preeclampsia in a limited numbers of studies. 5 In Sudan there are many studies conducted among pregnant women suffering from pregnancy complication. [6][7][8][9] Present study is first one conducted among Sudanese women to examine the frequency symptoms occurring in severe preeclamptic patients according to the levels of GGT and LDH, indicating multiorgan involvement and severity of the disease.…”
mentioning
confidence: 99%
“…On analyzing the above data it is clearly observed that there is significant rise in the LDH levels with increasing severity of the disease (P <0.001) which was seen in studies done by Rajoria L et al, Dev SV et al and Bhave NV et al [13,14,15].…”
Section: Discussionmentioning
confidence: 64%
“…In study by Nadkarni et al, 12 primigravida constituted 49% of total subjects in study group. Dave et al, 13 observed half of the cases in their study group as primigravida. Similar results were observed by Kheir et al 11 where 42% patients were primigravida.…”
Section: R E S U L T Smentioning
confidence: 77%
“…From this study, it can be concluded that elevated serum LDH level was associated with severity of pre-eclampsia. Dave A et al 13 conducted a study to find out the role of serum Lactate Dehydrogenase in prediction of adverse outcomes of pre-eclampsia and eclampsia i.e. severity of disease and occurrence of complications.…”
Section: Groupmentioning
confidence: 99%